El estado actual de las vacunas contra las drogas - Maura Epifanía Matus Ortega; Juan Carlos Calva Nieves; Susana Barbosa-Méndez; Alberto Salazar-Juárez (Centros de Integración Juvenil A.C., 2017)
Introduction: traditional approach for drug addiction includes treatment with psychological assistance alone or in combination with pharmacotherapy aimed at blocking the binding of addictive drugs to their specific brain receptors. Success rate of these traditional treatments is not satisfactory; hence, alternative approaches should be explored, including immunotherapy targeting drugs of abuse. Objective: this paper focuses in a review of available literature concerning immunotherapy for the following drugs of abuse: morphine, cocaine, nicotine and methamphetamine, in order to be used as part of addiction treatment. Method: a search was conducted for scientific reports in PubMed from January, 2005 to April, 2017, focused on the scientific principles, method, preclinical and clinical trials and their results on the field of vaccination against substance of abuse. Results: the available vaccines against substance abuse succeed in blocking the drug's reinforcing effects and mitigate drug-induced behaviors in preclinical trials in animal models. On the contrary, clinical trials in humans did not show therapeutic success. Discussion and conclusions: both academic research groups and pharmaceutical companies have published a number of pre-clinical research works on the field of vaccines for substance abuse, but thus far pre-clinical findings are not supported by results of the clinical trials. At present, efforts persist to improve vaccine efficacy and efficiency in humans for developing immunotherapy as a viable option for patients seeking treatment for drug addiction.----------------------- Introducción: por lo común, la adicción a las drogas se trata con psicoterapia y farmacología que evita la unión de las sustancias psicoactivas a receptores específicos en el cerebro. El resultado de estos tratamientos no ha sido del todo satisfactorio, por lo que el desarrollo de terapias más eficaces representa un reto constante para tratar las adicciones. Una alternativa a la farmacología antiadictiva es la vacunación activa dirigida contra las sustancias de abuso. Objetivo: esta revisión reúne la información disponible sobre los fundamentos y avances científicos en la generación de una terapia inmunológica, que coadyuve al tratamiento de la adicción a sustancias como la heroína-morfina, la cocaína, la nicotina y la anfetamina. Método: se consideraron los reportes científicos disponibles en PubMed -de 2005 a abril de 2017-, sobre los fundamentos, la metodología empleada, los estudios preclínicos y clínicos, y los resultados obtenidos en dichas investigaciones para generar vacunas contra las drogas. Resultados: las vacunas lograron mitigar los efectos producidos por las sustancias en los estudios preclínicos en modelos de estudio en animales; sin embargo, con pacientes humanos los resultados no han sido del todo satisfactorios. Discusión y conclusiones: a pesar de los esfuerzos realizados por diferentes grupos de investigación y compañías farmacéuticas para generar vacunas terapéuticas contra el uso de diferentes drogas, ninguna ha alcanzado la fase III de estudios clínicos. En la actualidad, se continúa con los esfuerzos para lograr que las vacunas contra las adicciones alcancen su máxima eficiencia y eficacia, y contribuyan al tratamiento de la adicción a las drogas.